SOCIAL-ETHICAL MARKETING IN BANKING: A FRAMEWORK FOR SUSTAINABLE GROWTH AND SOCIAL RESPONSIBILITY - Razzoqov Nozim Abdiroziqovich (Modern American Journals, 2025)
The relevance of the social-ethical marketing concept in banks is increasingly significant in today's competitive and changing global environment. With heightened competition, economic crises, and global financial shifts, commercial banks must not only focus on their financial gains but also embrace their social responsibilities. Implementing marketing strategies that prioritize social benefits is crucial for sustainable development in both the banking sector and society. Banks are expected to contribute not only by providing financial resources but also by actively promoting social well-being and improving the overall welfare of the population.